Physical Restraint Knowledge, Attitudes and Practices of Intensive Care Nurses in Turkey: The Effectiveness of an In-Service Training Program - YILMAZ, Elmas; KARAVELİ ÇAKIR, Selda; IŞIK ANDSOY, Işıl (Dokuz Eyul Universitesi Saglik Bilimleri Enstitusu, 2023)
Background: Intensive care nurses use physical restraints (PRs) to prevent critically ill patients from disrupting invasive medical equipment, but they may not recognize the negative or positive consequences. Purpose: The study was conducted with a quasi-experimental, single-group pretest-posttest design to evaluate the impact of PRs training on the knowledge, attitudes, and practices of intensive care nurses. Materials and Methods: The sample of the study consisted of 81 nurses. The data were obtained using a " The Individual Data" and the "Levels of Knowledge, Attitudes and Practices of Staff Regarding Physical Restraints Questionnaire." Descriptive statistics analyzed sample characteristics and Friedman's multiple comparison test performed to compare the effectiveness of training. Results: It was determined that all nurses applied physical restraint, and the rate of application of these on agitated and restless patients was 100%. Sixty-nine-point nine percent of the nurses decided on the physical restraint together with physicians, and 70.4% of them wanted to receive training about physical restraint. The nurses' attitude, and practice scores about the use of physical restraint in the post-intervention period and retest after 1 and 3 months increased significantly compared to the pre-intervention period (p=.000). Conclusion: This study showed that the physical restraint training given to the nurses was effective. The findings recommended to carry out in-service training to increase the knowledge levels of nurses about physical restraint and its application, repeat this training periodically and evaluate its effectiveness.
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi; Intensive care nursing; physical restraint; training; knowledge; attitudes; 3. Good health